Modelling willingness to pay for genetically modified Tela BT maize seed technology in Mpumalanga Province, South Africa - Phetoe, Patrick (My University, 2023)
Maize (zea maize) is the most important crop in South African grain production, providing nutrients to both humans and animals. It is a basic raw material for producing fuel, starch, oil and alcoholic beverages, as well as other economic benefits such as high yields and high income. Smallholder households have great reliance on agriculture that has shown little productivity improvement over a long period of time. This slow agricultural progression is largely attributed to a relatively low adoption and use of improved technologies, including hybrid seeds and fertilizers. The GM technology has been identified as one of the solutions to prevalent issues of food inadequacy brought about by population growth and dissatisfactory food production by people living in less developed countries. This study aimed at modelling willingness to pay (WTP) for genetically modified TELA® Bt maize seed technology in Mpumalanga Province, South Africa. The objectives of the study were to: profile socio-economic characteristics of smallholder maize farmers in Mpumalanga Province, assess farmers’ knowledge, attitudes, perceptions, and practices (KAPP) towards the TELA® Bt maize seed technology in Mpumalanga Province, South Africa, determine smallholder maize farmers’ WTP for the TELA® Bt maize seed technology in Mpumalanga Province, South Africa and analyse the determinant factors influencing smallholder maize farmers’ WTP for TELA® Bt maize seed technology in Mpumalanga Province. Data was collected from 289 farmers using purposive and multistage sampling techniques for the TELA® Bt maize, and snowball sampling techniques for the non-TELA® Bt maize farmers The descriptive statistics, which included cross tabulations and frequency distributions were used to describe socioeconomic characteristics of smallholder maize farmers and their typology, which addressed the first objective of the study. To address the second objective of the study, the Likert-scale and descriptive statistics were used to assess farmers’ knowledge, attitudes, perceptions, and practice (KAPP) towards the TELA® Bt maize seed technology in the study area concerned. A discrete choice experiment was deployed to solicit and compute the mean willingness to pay (MWTP) from the farmers, and finally, the Logistic regression model was used to identify determinant factors significant towards WTP for TELA® Bt maize seed technology. The results from the Logit scale for parameter estimates used to compute the mean willingness to pay (MWTP) showed that the additional amount farmers were willing to pay for a 1 kg bag of the TELA Bt maize seed technology was R6.59. The Logistic regression model empirical results showed that among farmers who were willing to pay for the TELA® Bt maize technology, household size, access to extension services, health perception, trust in government and benefits perception had a significant impact in their WTP. In light of the research findings, several policy suggestions were made that there should be a concerted effort from the side of the government to ensure frequent exposure of farmers to extension services. It also calls for the private institutions and NGOs responsible for the introduction of GM technology to work cohesively with the members of the public and the media to help facilitate the dissemination of relevant information about GM crops.
Thesis (M.Sc. Agriculture (Agricultural Economics)) -- University of Limpopo, 2023
Keywords: Maize (sea maize); South African grain production; Genetically Modified Tela BT maize technology; Mpumalanga Province; South Africa; Food -- Biotechnology; Corn -- Seeds -- Production; Grain; Corn -- Breeding; Agricultural biotechnology